2022
DOI: 10.3390/ijerph19052947
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Acceptance of New Technologies for Ageing in Place by People over 64 Years of Age

Abstract: Background: In the context of growing population ageing, technologies aimed at helping people age in place play a fundamental role. Acceptance of the implementation of technological solutions can be defined as the intention to use a technology or the effective use of it. Approaches based on the technology acceptance model (TAM) have been shown to have good predictive power for pre-implementation attitudes towards new technologies. Objective: To analyze the degree of acceptability of the use of new technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Our results are on the whole in line with those in the previous literature, especially regarding Southern European countries such as Italy [ 43 ], thus indicating that the majority of older people prefer to age in place/in their homes, at least even with a PCA, with little intention to consider moving elsewhere, e.g., to a nursing home or going to live with family/children [ 70 , 71 , 72 ]. Other authors [ 73 ] more specifically found that in later life, 37% of individuals would prefer to live independently at home.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are on the whole in line with those in the previous literature, especially regarding Southern European countries such as Italy [ 43 ], thus indicating that the majority of older people prefer to age in place/in their homes, at least even with a PCA, with little intention to consider moving elsewhere, e.g., to a nursing home or going to live with family/children [ 70 , 71 , 72 ]. Other authors [ 73 ] more specifically found that in later life, 37% of individuals would prefer to live independently at home.…”
Section: Discussionsupporting
confidence: 91%
“…A study explored in particular the role of loneliness and depression as risk factors for suicidal ideation among residents in nursing homes, and found that about 20% of them experienced such a thought [ 85 ]. Some interviewees also reported that, as was the case for PCAs, the nursing home is rejected for economic reasons, as highlighted by Chimento-Díaz and colleagues [ 70 ], who associated the degree of institutionalization with economic issues, in addition to the level of dependence of seniors.…”
Section: Discussionmentioning
confidence: 99%
“…However, as also emerged from our findings, many authors put in evidence that often older people do not use such alarms to call for help after a fall [ 81 , 82 ], since they consider these devices really intrusive, especially at night, and do not remember to wear them, even though alarms can increase their sense of safety at home [ 82 , 83 , 84 ]. Acceptance of technologies, aimed at supporting older people living alone, plays a fundamental role for ageing in place [ 85 ], and results from a study [ 38 ] showed indeed the need of wearable and easy to use alarms, as well as the need to introduce measures to promote the acceptance itself by seniors. Sarlo and colleagues [ 86 ] report different results, indicating that technology is almost appreciated among seniors living in North Italy (Bolzano), where the use of personal alarms has been successfully implemented, and whose signals (measurements of parameters and medical alarms) can be sent via text messages or e-mail, by mobile phone, both to family members and a Social Services Company.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity is also a consideration (Chimento-Díaz et al, 2022). PA-related technology may offer little to help older people struggling with barriers to being active such as pain and physical limitations (Perracini et al, 2017), fear of falling or beliefs about PA being unnecessary or too risky .…”
Section: Introductionmentioning
confidence: 99%